Health informatics in medical education in Peru: are we ready for digital health? - Quispe-Juli, Cender U. (2022)
Dear Editor, Digital health applications have demonstrated benefits in several healthcare outcomes therefore it has become a serious alternative to getting Sustainable Development Goals 2030 related to health (1). In recent years, Latin America is creating policies and strategies for digital health. Peru is one of the earliest countries in Latin America that establish policies for eHealth and digital health but its implementation in the real world is limited (2). It is well known that some medical schools have courses related to informatics, Health Informatics (HI), or even medical informatics but there is no evidence about how many of peruvian medical schools teach HI within their curricula or what content or topics are provided.